Physical simulation as a tool to understand friction stir processed X80 pipeline steel plate complex microstructures - Avila, Julian [UNESP]; Escobar, Julian; Cunha, Barbara; Magalhães, William; Mei, Paul; Rodriguez, Johnnatan; Pinto, Haroldo; Ramirez, Antonio (Elsevier, 2019)
The thermal cycles associated to friction stir welding and processing produce a wide range of microstructures, resulting in different mechanical behaviors along the weld. Most research efforts have focused on the development of welding parameters to obtain sound welds, yet there is still an opportunity for performance improvement based on the understanding of how microstructures are produced. This work explored the different microstructures obtained after physical simulation of an X80 pipeline steel, as a function of the cooling rate and the isothermal transformation temperature. The aim was to study the development of complex mixed microstructures under controlled conditions, in order to compare them to the ones obtained after friction stir processing. As result of the continuous cooling and isothermal thermal simulations, intermediated and high cooling rates, the microstructures matched with those found at the processed plates. These results might help developing a better cooling control after welding.
Keywords: Bainite; Continuous cooling transformation; Friction stir processing; Heat-affected zone; X80 pipeline steel